Decontamination of bioaerosols within engineering tolerances of aircraft materials - Frazey, John S., author; Reynolds, Stephen, advisor; Volckens, John, committee member; Keefe, Thomas J., committee member; Ellis, Robert P., committee member; Roy, Chad J., committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Keywords: bioaerosol; tolerance; material; decontamination; engineering; aircraft